PRO-KONTRA TERHADAP PERAYAAN MAULUD NABI DI MASYARAKAT MADURA - Mafruhah Mafruhah; Atnawi Atnawi (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2023)
Be born of propet Muhammad has been formed a holy ritual which unusually selebrated by moslem in every year as proved to amorousness to propet Muhammad. But, behind has selebrating that borned of propet Muhammad to occur dualism pro and contra from the member of a religious of moslem. There was fortification pro, but there was fortification contra. From this matter, author try to analised and gived way of middle (solution)), from that discoursed until not to occur the conflik in internal moslem. In that reseach was qualitatif with discribtion qualitatif reseach which relation of humaniora.